Negotiation and Determinants of Condom Use among Female Sex Workers in Denpasar - Putu Sukma Megaputri; Anak Agung Sagung Sawitri; Dewa Nyoman Wirawan (Universitas Udayana, 2016)
Background and purpose: Integrated Biological Behavior Survey (IBBS) in 2011 showed that use of condoms among clients of female sex workers (FSW) was low. This was likely associated with tha lack of negotiations by FSWs. This study aims to determine negotiation strategies and determinants of condom use among FSWs in Denpasar. Methods: Cross-sectional survey was conducted among 100 brothel FSWs selected using cluster random sampling in some locations in Denpasar. Data was collected through interviews using questionnaires on: socio-demographic characteristics, internal and external factors, condom negotiations and condom use. Questionnaire about condom negotiation was a modification of Condom Influence Strategy Questionnaire (CISQ) developed by Noar. Bivariate analysis was conducted using chi square test and multivariate analysis by logistic regression. Results: About 87% FSWs reported using condoms during the last sexual intercourse with their clients and 63% reported always used condom in the last week. About 37% of clients carried condoms when they visited FSWs and 58% of FSWs reported that they negotiated condom to their clients. Among 63% of clients who did not carry condoms, 92.1% of them eventually wear condoms after negotiated by FSWs. Negotiating strategy used by FSWs were direct request, conceptualizing relationships, risk information and deception. Significant factors associated with condom use were age of FSWs (AOR=4.1; 95%CI: 1.32-12.4), the availability of condoms (AOR=8.8; 95%CI: 2.8-27.7) and negotiations (AOR=3.9; 95%CI: 1.4-10.8). Conclusion: Most frequent negotiation strategy used was direct request to their clients. Significant factors associated with condom use were age of FSWs, availability of condom and condom negotiation.